Effect of Intercropping of Cotton and Peanut on Quantity and Quality of Soil Microorganisms - Usmonov Nodirjon Botiraliyevich (Genius Publishing Group, 2022)
The effect on the increase in the number and quality of soil microorganisms under the conditions of co-planting of cotton with peanut in the conditions of sandy soils of the desert region is highlighted.
Keywords: Intercropping; microorganisms; oligonitrophil